DOI: 10.11606/t.12.2020.tde-24062020-194331
|View full text |Cite
|
Sign up to set email alerts
|

Fecundidade, identificação racial e desigualdade

Abstract: INCT para Mudanças Climáticas. As opiniões, hipóteses e conclusões ou recomendações expressas neste material são de responsabilidade do autor e não necessariamente refletem a visão da FAPESP e do CNPq. Na atual conjuntura de cortes de verbas para pesquisa é importante acrescentar que, desde a graduação, as bolsas e a universidade pública foram determinantes para o meu desenvolvimento como pesquisador, decisivas na minha trajetória e, por isso, ao menos neste aspecto, tenho um profundo sentimento de gratidão co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…More recently, some studies have shown a change in racial perception among Brazilians, with an increase in the share of individuals self-classifying as Black or Brown ( 28 ). Although causal research on this topic is scant, some research has shown that public policy and media representation can affect how individuals classify themselves ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some studies have shown a change in racial perception among Brazilians, with an increase in the share of individuals self-classifying as Black or Brown ( 28 ). Although causal research on this topic is scant, some research has shown that public policy and media representation can affect how individuals classify themselves ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%